KENDALA YANG DIHADAPI GURU DALAM PEMBELAJARAN SENI RUPA DI SMP NEGERI LIMA KAUM TANAH DATAR - Yosi Isvandi Ary; Eswendi .; Ramalis Hakim (Serupa The Journal of Art Education, 2012)
Abstract Components in the implementation of learning art constrained by the "many" are: (a) Using the learning resources that have been, (b) Using instructional media / lab equipment that has been determined, (c) Present the subject matter systematically. (3) assessment of learning achievements of art students in the category of "moderate" with an average score of 2.80. Component activities art assessment of learning achievement of students who get the constraint that "many" are: (a) Assess the learning outcomes appropriate based on predetermined criteria, (b) Check the answer / provide achievement test scores based on the indicators / criteria of performance been determined, (c) to analyze the results. (4) the follow-up assessment of learning achievement of students in the category of "moderate" with an average score of 3.00. All components also are in the medium category. Keywords: Constraints, Learning, Assessment, SMP N Five Tribe